UTILIZATION OF ORGANIC WASTE USING TECHNIQUES BIOREACTOR SUBMARINE IN PATI CENTRAL JAVA - Sofiyah, Siti Nur; Fikri, Achmad Ali (RUMPHIUS, 2021)
One of the waste that is often found is organic waste. The existence of this waste needs to be handled so that it does not pollute the environment and has more use value. Through proper processing, organic waste can be used as organic fertilizer and biogas. One of the techniques used for this processing is to use the submarine bioreactor technique. This study aims to explore the processing of organic waste in Ngemplak Kidul Margoyoso Pati Village using the submarine bioreactor technique. This research is a field research with a qualitative approach and then analyzed descriptively. The stages of processing organic waste with the submarine bioreactor technique are enumeration, then the stage of producing decomposers, the stage of producing fertilizer and the stage of producing biogas. The advantage of this submarine bioreactor technique is that if a leak occurs it can be detected and can distribute gas over long distances and is safe in its use. Even though it takes a long time and costs a lot, this bioreactor is proven to be able to produce effective fertilizer and biogas for large quantities of plants. After this research, it is hoped that it will provide an overview of waste processing using the submarine bioreactor technique and can become a reference for village governments or other institutions to implement in their area as a solution for organic waste processing.